Pharmacokinetics of Amoxicillin/Clavulanic Acid Combination after Oral Administration of New Suspension Formulations in Human Volunteers: Pharmacokinetics of coamoxiclave suspension - Mostafavi, Sayed Abolfazl; Dormiani, Kianoosh; Khazaie, Yahya; Azmian, Abbas; Zargarzadeh, Mohammad Reza (Iranian Journal of Pharmaceutical Sciences, 2006)
The pharmacokinetic properties of amoxicillin and clavulanic acid when used alone or in combination may be different and show interaction between these two agents that might decrease the absolute bioavailability of clavulanic acid. In an open, randomized, replicated Latin square under fasting condition, pharmacokinetics of new formulations of amoxicillin/clavulanic acid were compared with a reference formulation after single dose administration in 15 healthy male volunteers. Subjects were given equal molar doses of new suspension formulations of amoxicillin/clavulanic acid (312 mg/5 ml or 156 mg/5 ml) or Augmentin® (312 mg/5 ml) as the reference product. The wash-out period was one week between the administrations of these antibacterial agents. Blood samples were collected exactly before and after drug administration of each of the formulations at different time points up to 6 h. The concentrations of the antibiotics in plasma were measured by validated HPLC methods. Three formulations exhibited a similar mean C max of about 7.5±1.6 mg/l after Tmax of about 75±25 min. for amoxicillin and Cmax of about 2.5±0.6 mg/l after Tmax of about 61±15 min. for clavulanic acid. The AUC0-inf (total area under the curve) for amoxicillin was about 1278±172 g.min/ml and it was about 354±66 g.min/ml for clavulanic acid. There were no significant differences in pharmacokinetic parameters among these formulations. Pharmacokinetic parameters of amoxicillin and clavulanic acid found in this study were similar to previously published data. The two generic formulations investigated in this study proved to be bioequivalent with brand-name Augmentin® with regard to the pharmacokinetic parameters Cmax, AUC0-t, AUC0-inf and Tmax. Moreover, the parametric confidence intervals (90%) for the ratio of the Cmax, Tmax, AUC0-t, and AUC0-Q values lie between 0.8-1.2 based on log transformed values. We may conclude that the two new formulations are bioequivalent with the reference suspension and could be considered equally effective in medicinal practice. Moreover, there were no interaction in pharmacokinetic parameters between amoxicillin and clavulanic acid. No serious adverse event was observed with the studied drugs.